Pengaruh Green Competitive Advantage, Green Innovation dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ilyas Nur Imam; Nindito, Marsellisa; Gurendrawati, Etty (Jurnal Ilmiah Wahana Akuntansi, 2024)
The purpose of this research was to test and analyze the effect of green competitive advantage, green innovation and company size on company value. This research uses secondary data sources from annual report and sustainability report on companies in the basic materials sector on the Indonesia Stock Exchange in 2021-2022 with a purposive sampling technique. The analysis technique used is panel data regression. The results of this research prove that green competitive advantage has a significant positive effect on company value, green innovation has a significant positive effect on company value, while company size has no effect on company value. Companies that have production processes and products that support green competitive advantage and green innovation will increase company value. So this research prove and provides information for company management and the public that there are many factors that can influence increasing the value of the company.